Scenarios of fuel vector trajectories in the Italian road vehicle fleet to 2030 and their impacts on EU GHG reduction targets - Davide Di Domenico; Carlo Beatrice; Ilaria Henke; Mariarosaria Picone; Armando Cartenì; Ennio Cascetta (Frontiers in Future Transportation)
The transport sector’s decarbonization remains a critical challenge in reducing greenhouse gas (GHG) emissions and achieving the EU Green Deal 2030 targets (−43.7% with respect to 2005). This article develops forecasts for 2030 to assess the potential reduction in tank-to-wheel (TtW) and well-to-wheel (WtW) GHG emissions within the Italian road transportation sector. Two tendential scenarios, namely, “High Decarbo” and “Moderate Decarbo,” are constructed based on differing hypotheses and on adoption rates of measures and policies aimed at promoting sustainable transportation (e.g., subsidies for electric vehicles) that are already in effect. The “Moderate Decarbo” forecasts project a 12% TtW and a 15% WtW GHG emissions reduction compared to 2005 levels. Under favorable assumptions, GHG emissions could potentially be reduced by 28% TtW and 33% WtW, nearing EU targets but still falling below them. The impact of electrification has been broken down, and the hybrid electric vehicle (HEV) contribution on GHG reduction is expected to be very close to that of battery electric vehicles (BEVs), underlining the advantages that an increased spread of HEVs might have, in addition to the BEVs. The introduction of the law-required quantities of second-generation biofuels is the main driver for the higher WtW reductions. Two more “trend-breaking” 2030 scenarios are developed in which biofuels are spread, maximizing the Italian production capabilities to abate the environmental impact of the freight sector. In the High Decarbo scenario, the WtW GHG emissions reduction is up to 40%, demonstrating the impact that a smart use of biofuels might have.